Performance of Lead-Acid Battery for Off-Grid Solar System - Kamian, Mohammad Amirul Amin; Abd Razak, Mohd Fadly (Progress in Engineering Application and Technology, 2023)
The use of a storage device in applications using renewable energy plays a crucial role in ensuring effective functioning. In solar photovoltaic (PV) applications, a storage device is an essential component in order to continue supplying electricity to the load after the sun has set. In the course of this investigation, the information obtained from Lead-Acid type batteries will be evaluated in order to get a better understanding of such batteries’ capabilities and performances, including the Depth of Discharge (DOD) and the State of Charge (SOC). If the performance of the battery can be improved, then not only will there be a notable decrease in the cost of the energy, but there will also be an increase in the system’s level of dependability. A battery is required in a PV system in order to store the additional energy that is generated by the sun, which can then be released back into the system when it is required. To put it another way, to improve the performance of a system, we need to improve the performance of the battery. In this study, the factors that have been shown to have a significant influence in achieving optimal performance are analyzed. Temperature and load current are the two characteristics that have the most significant impact on the performance of the battery. It has been discovered that the capacity of the battery decreases when the discharge current is large, and that the opposite is true when the current is low.